Perfect match [large type] - Michaels, Fern (Wheeler Publishing, a part of Gale/Cengage Learning, 2015)
NFL star Jake Masters has a spinal injury that ended his career. Now confined to a wheelchair, he's unwilling to take a chance on another risky surgery that could restore his mobility. But his twin sister Beth has no intention of letting him languish there forever, and she's gifting a matchmaking business to Jake, whether he likes it or not. It's soon clear that he needs an assistant. Enter Gracie Sweet, whose slender frame belies a take-no-charge toughness that would put any linebacker to shame.